UJI AKTIVITAS ANTIMIKROBA EKSTRAK DIETIL ETER DAUN GAMAL (Glyricidia sepium (JACQ.) STEUD.) SECARA KLT-BIOAUTOGRAFI - A. Mumtihanah Mursyid (As-Syifaa Jurnal Farmasi, 2011)
Studies have been conducted testing the antimicrobial activity of leaf extracts gamal (Glyricidia sepium (Jacq.) Steud.). Preliminary research conducted by the screening test using the test microbe Staphylococcus aureus, Salmonella typhi, Streptococcus mutans, Staphylococcus epidermidis, Pseudomonas aeruginosa, Escherichia coli, Vibrio sp, Bacillus subtilis and Candida albicans to extract ethanol, diethyl ether and n-butanol from leaf gamal (Glyricidia sepium (Jacq.) Steud.) with levels of 1 mg / ml. The results showed that the diethyl ether extract active has hampered the growth of microbes Staphylococcus aureus, Escherichia coli, Streptococcus mutans, Salmonella typhi, and Pseudomonas aeruginosa.Tests for antimicrobial activity against diethyl ether extracts of leaves gamal (Glyricidia sepium (Jack). Steud.) Carried out by liquid dilution method to determine the value of MIC at a concentration of 0.025%, 0.05%, 0.1%, 0.2%, 0, 4%, 0.8% and 1.6%, followed by etching in a solid medium to determine the price of teaching. The results showed that the MIC could not be determined due to turbidity test solution, while the price KBM 0.05% for Escherichia coli, Salmonella typhi 0.4%, 0.8% for Pseudomonas aeruginosa and Streptococcus mutans and 1.6% for Staphylococcus aureus,To estimate the class of compounds that provide antimicrobial activity test carried out TLC-Bioautografi. Obtained the best results from the separation of compounds by TLC using the eluent n-hexan: ethyl acetate (2:1). TLC-Bioautografi test results showed that the spots with Rf 0.27 and Rf value of 0.363 provides antimicrobial activity against Escherichia coli, Rf 0.363 against Pseudomonas aeruginosa, and Rf 0.45 against Staphylococcus aureus, Salmonella typhi, and Streptococcus mutans. The results of identification of chemical components showed that the active compounds gave positive results in spotting penampak phenol group at Rf 0.27 and Rf 0.36 and Rf 0.45 on steroids.Key word: antimicrobial activity, screening, TLC-Bioautografi, Gamal (Glyricidia sepium (Jack).Steud.)